1972
DOI: 10.1136/bmj.2.5814.616
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis with Necrotizing Enterocolitis in Premature Babies

Abstract: SummaryEleven premature babies developed necrotizing enterocolitis in an epidemic of gastroenteritis and salmonella infection. This occurred in one of two premature baby wards over a period of 10 weeks. All affected babies had severe gastroenteritis and six had salmonella infection. No cases of necrotizing enterocolitis occurred in the unaffected ward during the same period. All other possible factors which might have predisposed to necrotizing enterocolitis occurred with equal frequency in both wards.There se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…pathogen-specific NEC) differing greatly. In 1972, Stein et al reported one of the first outbreaks consisting of 11 cases of NEC in a single nursery in South Africa over a 10-week period 10. Chappell and Dinner reported an outbreak involving 20 cases over a 3-week period 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pathogen-specific NEC) differing greatly. In 1972, Stein et al reported one of the first outbreaks consisting of 11 cases of NEC in a single nursery in South Africa over a 10-week period 10. Chappell and Dinner reported an outbreak involving 20 cases over a 3-week period 29.…”
Section: Discussionmentioning
confidence: 99%
“…No formal or consistent approach has been applied to these reports, however, regarding the definition and timing of apparent outbreaks or the cases associated with them. The case definition applied during outbreak investigations has often included suspected NEC and gastroenteritis cases, with outbreak durations of 8 to 10 weeks 1021…”
mentioning
confidence: 99%
“…Mizrahi and colleagues in NYC cultured blood and peritoneal fluid from patients with disease and demonstrated a predilection for Gram negative bacteria, particularly E. Coli as offending agents associated with NEC 12 . Additional studies in the early 1970’s showed that ‘epidemics’ of NEC occurred in some NICU’s, and in one of the first reports, Stein et al showed that Salmonella organisms were involved in 11 consecutive cases 13 . Nonetheless, many cases of NEC were not associated with bacterial organisms in the blood, and further investigation suggested that intestinal bacteria might initiate NEC by activating the inflammatory response.…”
Section: Effect Of Microbiomementioning
confidence: 99%
“…This was emphasized by Lloyd (1969) as an important etiology of gastroi.ntestinal perforations of the newborn infant. The high incidence of infection found in NEC has been reported by many authors which is mostly caused by gram-negative microorganisms such as, Salmonella (Stein et al, 1972), Klebsiella (Hill et al,, and E. coli (Speer et al, 1976). These implicate enteric bacteria in 1he pathogenesis of the disease.…”
Section: Et!iology and Pathogenes·1smentioning
confidence: 96%